Halal Tourism in Theory of Planned Behavior: Intention to Recommend Variable Analysis - Farizkhan, Mohammad Medwin; Masnita, Yolanda; Chrisjatmiko, Kurniawati (Journal of Social Research, 2023)
The purpose of this research is to examine hypotheses based on the theory of planned behavior (TPB) regarding the relationship between consumer behavior and behavioral factors of recommendation intention in halal tourism. Indonesia, with the world's largest Muslim population, stands as a significant market for halal tourism. However, despite being a prominent halal tourist destination, Indonesia lags behind Malaysia, which raises questions about the dynamics of consumer behavior in promoting halal tourism in Indonesia. Consumer satisfaction has been identified as a crucial determinant of behavioral intentions influenced by behavioral factors. To investigate this phenomenon, cross-sectional data were collected from Muslim tourists using quantitative approaches through questionnaires. Structural equation model (SEM) analysis techniques were applied to draw meaningful insights from the data. The findings revealed that the coefficient of halal attitude significantly impacts the level of satisfaction among tourists, ultimately motivating them to recommend halal tourism in Indonesia. These results validate the role of intervening satisfaction proposed within the framework and provide deeper insights into the variables and mediators of perceived behavior and attitudes. These findings are instrumental in understanding the development of theoretically planned behaviors in the context of halal tourism. Understanding the factors influencing consumer behavior and recommendation intention in halal tourism can be crucial for enhancing Indonesia's position as a top halal tourist destination. By catering to the specific needs and preferences of Muslim tourists, Indonesia can elevate its appeal and attract a larger share of the growing halal tourism market.